Penerapan Keggel Exercises Untuk Mengatasi Inkontinensia Urine Refleks Pada Lansia Dengan Cedera Tulang Belakang: Studi Kasus - Nova Natalia Beba; Juliana Neng Rifka Sarman; Feybe Geraldine Lucia (Yayasan Ekselensi Daya Indonesia, 2025)
Spinal cord injury (SCI) is a condition that injures the spine either as a whole or only part of the spinal segment. Kegel exercise is an exercise to strengthen the pelvic floor muscles, or an exercise that aims to strengthen the pelvic floor muscles, especially the pubococcyx muscles, so that a person can strengthen the muscles of the urinary tract. Urinary incontinence is the involuntary discharge of urine in sufficient quantity and frequency that causes health or social, hygienic, psychosocial, and economic problems. Objective: Describe nursing care for applying Keggel exercise therapy to overcome reflex urinary incontinence in the elderly with spinal cord injury. Method: This study uses a descriptive case study method. The data collection methods provided are interviews and observations. The instrument used is an assessment of urine elimination patterns. The results of the assessment indicate that the client is experiencing incontinence problems. The nursing diagnosis raised is reflex urinary incontinence related to damage to impulse conduction above the reflex arc, according to the signs and symptoms in the SDKI. The intervention given was 9 days of intervention by previous research, which applied Kegel exercise therapy. After applying the Keggel exercise for 9 meetings, the client's urine scale results decreased. It is expected that from the results of this case study, respondents can apply Keggel exercise techniques regularly and independently.